Systematic Analysis of the R2R3-MYB Family in Camellia sinensis: Evidence for Galloylated Catechins Biosynthesis Regulation - Li, Jingyi; Liu, Shaoqun; Chen, Peifen; Cai, Jiarong; Tang, Song; Yang, Wei; Cao, Fanrong; Zheng, Peng; Sun, Binmei (Frontiers in Plant Science, 2022)
The R2R3-MYB transcription factor family regulates metabolism of phenylpropanoids in various plant lineages. Species-expanded or specific MYB transcription factors may regulate species-specific metabolite biosynthesis including phenylpropanoid-derived bioactive products. C. sinensis produces an abundance of specialized metabolites, which makes it an excellent model for digging into the genetic regulation of plant-specific metabolite biosynthesis. The most abundant health-promoting metabolites in tea are galloylated catechins, and the most bioactive of the galloylated catechins, epigallocatechin gallate (EGCG), is specifically relatively abundant in C. sinensis. However, the transcriptional regulation of galloylated catechin biosynthesis remains elusive. Species-expanded or specific MYB transcription factors may regulate species-specific metabolite biosynthesis. This study mined the R2R3-MYB transcription factors associated with galloylated catechin biosynthesis in C. sinensis. A total of 118 R2R3-MYB proteins, classified into 38 subgroups, were identified. R2R3-MYB subgroups specific to or expanded in C. sinensis were hypothesized to be essential to evolutionary diversification of tea-specialized metabolites. Notably, nine of these R2R3-MYB genes were expressed preferentially in apical buds and young leaves, exactly where galloylated catechins accumulate. Three putative R2R3-MYB genes displayed strong correlation with key galloylated catechin biosynthesis genes, suggesting a role in regulating biosynthesis of epicatechin gallate (ECG) and EGCG. Overall, this study paves the way to reveal the transcriptional regulation of galloylated catechins in C. sinensis.